ACTIVE CLOAKING FOR FINITE CLUSTERS OF PINS IN KIRCHHOFF PLATES - O'Neill,J; Selsil,O; Haslinger,SG; Movchan,NV; Craster,RV (SIAM Journal on Applied Mathematics, 2017)
This paper considers active cloaking of a square array of evenly spaced pins in a Kirchhoff plate in the presence of flexural waves. Active sources, modeled as ideal point sources, are represented by the nonsingular Green's function for the two-dimensional biharmonic operator and have an arbitrary complex amplitude. These sources are distributed exterior to the cluster, and their complex amplitudes are found by solving an algebraic system of equations. This procedure ensures that selected multipole orders of the scattered field are successfully annulled. For frequencies in the zero-frequency stop band, we find that a small number of active sources located on a grid is sufficient for cloaking. For higher frequencies, we achieve efficient cloaking with the active sources positioned on a circle surrounding the cluster. We demonstrate the cloaking efficiency with several numerical illustrations, considering key frequencies from band diagrams and dispersion surfaces for a Kirchhoff plate pinned in a doubly periodic fashion.